PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DANDISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI PT. XYZ JAKARTA SELATAN - Fauzan, Fauzan; Agustini, Agustini; Pitaloka, Fajar; Sudjana, Krisna (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this study is to determine and analyze the influence of leadership style, motivation and work discipline on employee performance at PT. XYZ South Jakarta. The type of research used is explanatory research with research methods in the form of data collection using questionnaires. The data analysis model used is multiple linear regression analysis. Sample selection is done by nonprobability sampling. The sample amounted to 100 respondents, using multiple linear regression analysis. The regression test results showed that 52.9% of employee performance factors could be explained by leadership style, motivation and work discipline while the remaining 47.1% were explained by other factors not studied in this study. While the results of the F test show that simultaneously the variables of leadership style, motivation and work discipline simultaneously have a positive and significant effect on employee performance with the results of the analysis, namely the value of Fcalculate (38,088) > Ftable (2,700). The results of the t test showed that the leadership style variable showed the results of the tcount analysis (1,998), the motivation variable showed the results of the tcount analysis (3,268) and the work discipline variable showed the results of the tcount analysis (2,274) where the ttable (1,98397) then partially the three valiabels had a positive and significant effect on employee performance at PT. XYZ South Jakarta. The dominant variable affecting employee performance is motivation.